PENGARUH GAME-BASED LEARNING TERHADAP PRESTASI BELAJAR SISWA DI PENDIDIKAN VOKASI: TINJAUAN PUSTAKA SISTEMATIS (2021–2026) - Danil Oktaviansyah; Donny Fernandez; Hasan Maksum; Wagino Wagino (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Learning achievement in vocational education remains a persistent concern, as conventional teacher-centred instruction often fails to engage students or to build cognitive, affective, and psychomotor competence in technical subjects. Game-Based Learning (GBL) is increasingly proposed as an innovative model to raise motivation and achievement; however, syntheses that map how GBL affects learning achievement specifically in vocational and technical education remain scarce. This Systematic Literature Review (SLR) synthesises Scopus-indexed studies (2021–2026) on the effect of Game-Based Learning and gamification on student learning achievement, motivation, and engagement in vocational and technical education. Following PRISMA 2020 guidelines, an initial Scopus search via Publish or Perish (PoP) version 8 was conducted; records were screened for the 2021–2026 window and topical relevance, and the core studies were retained for qualitative thematic synthesis, complemented by VOSviewer keyword co-occurrence mapping. This article reports the introduction, literature review, research questions, and method; results and discussion will be completed after metadata retrieval in PoP. The review is expected to clarify the magnitude and direction of GBL effects across cognitive, affective, and psychomotor domains, the dominant game platforms (including Kahoot), and the research gap regarding GBL in vocational practical subjects.Keywords: Game-Based Learning; Gamification; Learning Achievement; Vocational Education; Kahoot; Systematic Literature Review; PRISMA 2020.